The quality of orientation for newly hired nurses in acute care settings in a university hospital: A cross-sectional study - Rauta, Satu; Junttila, Kristiina; Strandell-Laine, Camilla; Peltokoski, Jaana; Haapa, Toni (Elsevier BV, 2025)
Aims: This study aims to describe how newly hired nurses assess the quality of the orientation in acute care settings in a university hospital. Background: Orientation for newly hired nurses in acute care settings, where special competence, ability to collaborate with different professional groups, and wide technical and technological skills are required, is crucial to ensure patient safety and high-quality standards in nursing care.
Methods: A cross-sectional study design was applied. Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines were followed. A convenience sample consisted of nurses (N = 120) from nine operating rooms and four intensive care units. The participants were newly hired (for one year). The data was collected via an online questionnaire including three parts: 1) socio-demographic and orientation-related items; 2) the Comprehensive Orientation Process Evaluation (OPE-instrument (c) Peltokoski, 2016); and 3) an adopted version of the Clinical Learning Environment, Supervision and Nurse Teacher Scale (CLES+ T Scale (c) Saarikoski et al., 2008). Descriptive and bivariate statistical analyses were used.
Results: 66 newly hired nurses answered the survey; the response rate was 44 %. The comprehensive orientation process was assessed as follows: goals and responsibilities, and standardized content of the comprehensive orientation process (mean 3.98), implementation of the comprehensive orientation process (mean 3.95), and evaluation of the comprehensive orientation process (mean 3.31). The quality of the clinical learning environment and supervision was assessed as follows: premises of learning on the ward (mean 4.04), supervisory relationship (mean 4.04), atmosphere on the ward (mean 3.77), and premises of nursing care on the ward (mean 3.65). Setting and achieving learning goals and professional growth supporting orientation were most often statistically significantly associated with a comprehensive orientation process and a clinical learning environment and supervision.
Conclusion: Although newly hired nurses assessed the quality of the orientation at an appropriate level, evaluation should be systematically performed at different checkpoints of the orientation process. Learning goals should be set individually, and their achievement monitored to confirm the quality of the orientation.